2015
DOI: 10.1186/s12906-015-0880-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the aqueous extract of the aerial parts of Monsonia angustifolia E. Mey. Ex A. Rich., on the sexual behaviour of male Wistar rats

Abstract: BackgroundMonsonia angustifolia (Geraniaceae) is a medicinal plant traditionally used in South Africa to increase libido and to treat erectile dysfunction.MethodsIn-vivo aphrodisiac activities of the crude extracts of the plant prepared in water at 3, 30 and 300 mg/kg body weight were evaluated for 7 days using sildenafil citrate (Viagra) and 1 % ethanol in distilled water as positive and negative controls respectively. Male rats were selected and monitored in each group for sexual behaviour by exposing them t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 26 publications
7
37
0
Order By: Relevance
“…The selected doses (75, 150, and 300 mg/kg b.w.) in this study were informed by the averages of daily consumed regimens and reported pharmacological study on the extract [6]. Generally, the fact that 28-day daily dose treatment with the extract elicited no clinical signs of toxicity, morbidity, or mortality across all the treatment groups may be a tenable inference that the extract of M. angustifolia is unlikely to be toxic at the tested doses over the observation period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The selected doses (75, 150, and 300 mg/kg b.w.) in this study were informed by the averages of daily consumed regimens and reported pharmacological study on the extract [6]. Generally, the fact that 28-day daily dose treatment with the extract elicited no clinical signs of toxicity, morbidity, or mortality across all the treatment groups may be a tenable inference that the extract of M. angustifolia is unlikely to be toxic at the tested doses over the observation period.…”
Section: Discussionmentioning
confidence: 99%
“…Liver and kidney function tests are crucial in toxicological evaluation of plant extracts due to the utmost involvement of these organs in xenobiotic biotransformation [6]. Significantly increased serum activities of ALP, ALT, AST, and GGT are closely associated with hepatic injury [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The episodes of the phases of mating were recorded with an audio video‐cassette (Sony Handycam, DCR‐TRV260) mounted above the test arena. The male sexual behaviour parameters recorded for the 30 min observatory period (Fouche, Afolayan, Wintola, Khorombi, & Senabe, ), which commenced immediately after the female rats were paired with the male rats were:…”
Section: Methodsmentioning
confidence: 99%
“…Monsonia angustifolia (Geraniaceae) is a medicinal plant traditionally used in South Africa to increase libido and to treat erectile dysfunction. Fouche, Afolayan, Wintola, Khorombi, and Senabe () investigated aphrodisiac activities of the crude aqueous extracts of M. angustifolia (Geraniaceae) at 3, 30 and 300 mg/kg body weight and evaluated different sexual parameters during a 7‐day experimental study on male rats. It was found that the extract different dose significantly ( p < .05) increased the mount frequency, intromission frequency, ejaculation frequency, ejaculation latency and serum hormone concentrations.…”
Section: Medicinal Plants Andplant‐derived Products Used As Aphrodisimentioning
confidence: 99%